Pengaruh penambahan rumput laut (Eucheuma cottonii) pada pengolahan fishstick ikan Toman (Channa micropeltes) - - Aryani; Tyas Wara Sulistyaningrum; - Norhayani (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
The research aims to get new innovative work to process fishstick which is rich of fiber and nutritious by adding seaweed through diversification technology of fish processing by using fish caught and seaweed which are quite abundant in several areas in Central Kalimantan Province. The research using experimental method using simple RAL with 4 treatments on the additional seaweed flour (Eucheuma cottonii) 0%, 1%, 3% and 5%. Research activities including chemical test (water, protein, and fiber) and organoleptic test. Based on chemical test on water, protein, and fiber content show different results. The lowest of average water content is showed by adding 3% of seaweed flour. The higest precentage is showed without additional of seaweed flour treatment (control) the higest colour average will get by adding 5% of seaweed flour. The higest aroma will show on additional 1% seaweed treatment. The higest taste and crispiness show on additional 3% of seaweed flour. Key words : Seaweed, snack, fishstick.